ЭФФЕКТИВНОСТЬ ДВОЙНОЙ ДЕЗАГРЕГАНТНОЙ ТЕРАПИИ У ПАЦИЕНТОВ С ИШЕМИЧЕСКОЙ БОЛЕЗНЬЮ СЕРДЦА В СОЧЕТАНИИ С САХАРНЫМ ДИАБЕТОМ 2 ТИПА ПОСЛЕ СТЕНТИРОВАНИЯ КОРОНАРНЫХ АРТЕРИЙ - О. Ю. Калугина; В. П. Носов; H. Guzman; R. Erbel (SINAPS LLC, 2014)
The article reviews the state of vascular-platelet hemostasis in patients with coronary heart disease and diabetes mellitus type 2. It was shown the less efficiency and the higher incidence of resistance to the classic double antiplatelet therapy in these patients after coronary stenting.